1998
DOI: 10.1075/eww.19.2.02dub
|View full text |Cite
|
Sign up to set email alerts
|

From Accent to Marker in Cajun English

Abstract: The English of bilingual Cajuns living in southern Louisiana has been described as an accented variety of English, the result of interference from French. In order to investigate this proposition, we present a variationist study of four features of Cajun English: 1) the interdental fricatives /θ, ð7 realized by the dental stops [t, d]; 2) the failure to aspirate the stops /p, t, k/; 3) the monophthongization of /ai/ and 4) vowel nasalization. The data for this study are taken from the Cajun French/ English Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…In comparison, the white participants showed a significant increase of use across generations in weren't leveling and a significant decrease in verbal –s marking with third person plural noun phrases; all other grammar structures showed minimal change. Dubois and Horvath (1998; 1999) have documented similar structure specific changes across generations in phonological patterns that have been historically tied to Cajun English in Louisiana. In their studies, some structures show a decrease in use from older to younger speakers, others show an increase, and still others show a v-shape pattern of change, with high rates of use in older and younger speakers, and low rates of use in middle-age speakers.…”
mentioning
confidence: 85%
“…In comparison, the white participants showed a significant increase of use across generations in weren't leveling and a significant decrease in verbal –s marking with third person plural noun phrases; all other grammar structures showed minimal change. Dubois and Horvath (1998; 1999) have documented similar structure specific changes across generations in phonological patterns that have been historically tied to Cajun English in Louisiana. In their studies, some structures show a decrease in use from older to younger speakers, others show an increase, and still others show a v-shape pattern of change, with high rates of use in older and younger speakers, and low rates of use in middle-age speakers.…”
mentioning
confidence: 85%
“…In terms of contemporary vowel phonology, Creoles and Cajuns share a range of local features that continue to be distinct from southern norms. Dubois and Horvath (1998a, 1998b, 2001, 2003c, 2004 have also demonstrated the linguistic effects of a recent cultural revival among younger Cajuns (Dubois & Melançon 1997), who have readopted and revitalized a variety of distinctive phonetic, lexical, and morphosyntactic features previously associated with their grandparents' generation.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies of Cajun English (Dubois & Horvath 1998a, 1998b, 2001, 2003c, 2004Wroblewski, Strand, & Dubois 2010) have demonstrated that while it shares many morphosyntactic and phonological features with Southern English, there is evidence that it maintains a "distinctive coherence as a separate dialect" (Dubois & Horvath 2004:411). Dubois andHorvath (2003a, 2003b) also find that the English spoken by white Cajuns and Creole African Americans in southern Louisiana shares many characteristics; however, neither schwar nor postvocalic /r/ has been discussed in previous research on Creole AAE.…”
Section: Schwar In the South Louisiana And Aaementioning
confidence: 99%
“…Language varieties are associated, among other factors, with social class (Labov, 1964;Ash, 2002) and ethnic identity (Rose, 2006;Mendoza-Denton, 1997;Dubois and Horvath, 1998). As a case study, we evaluate the efficacy of LID systems in identifying English tweets containing health lexicons, across regions with varying Human Development Index (HDI).…”
Section: Case Study: Health Monitoringmentioning
confidence: 99%